Новітні дослідження напольного валу городища Коровель - Жигола, В.С. (Археологія, 2014)
Подано матеріали останніх досліджень північно-східного кута зовнішнього валу городища Коровель, а також розглянуто питання конструктивних особливостей і часу функціонування укріплень. Новейшие раскопки северовосточного угла укреплений городища Коровель позволили исследовать как уже из вестные элементы уреплений, так и новые особенности — систему канав от деревянных конструкций городень, которые можна разделить на две группы.
К первой группе пренадлежат канавы 5, 8 и 9 (ширина до 0,2 м), так как канавы 8 и 9 параллельны и сооруже ны рядом, что соответствует стенам двоих соседних городень. Канава 5 перпендикулярна канаве 8 и вместе с ней образует стены одной городни. Засыпки городень прослеживаются в стратиграфии западной стенки раскопа 27. Учитывая полную нивелировку укреплений второй половины Х в., данные городни можно отнести ко времени возобновления валов в конце ХІ в. Канавы 3, 4, 6 и 7 (ширина 0,3—1,0 м) относятся ко второй группе. Канавы 6 и 7 почти перпендикулярны и имеют общий угол, то есть принадлежат одной городне. Канава 4 параллельна канаве 6 и относится к следующей соседней городне. Канава 3 в общем перпендикулярна предыдущим и почти парал лельна канаве 7, но выкопана в 2,0 м (северная часть) и 3,0 м (южная часть) от последней. Такая трапециевидная форма может свидетельствовать о конструктивной особенности городень на месте поворота вала.
Обе группы канав имеют разную ориентацию по сторонам света и взаимопересекаются под углами около 35— 50 °, что свидетельствует об отстройке вала и его новую трассу в ХІІ в. изза уничтожения или капитальном ремон те северовосточного угла укреплений. Более позднее время сооружения второй группы канав подтверждается их совпадением с контурами заполнения городень ХІІ—ХІІІ вв.
С нижней части пахотного слоя фиксируется заполнение двух рядов городень ХІІ—ХІІІ вв. Внешний (северо восточный) ряд выходил на край террасы; размер зафиксированого пятна 3,00 × 2,00—2,25 м, что полностью соот ветствует параметрам большинства исследованых городень. На уровне выявления заполнения городень обнару жен угол истлевшей деревянной конструкции, образующей угол сруба городни. В заполнении городень встречены материалы и керамика Х—ХІІ вв.
Обращено также внимание на столбовые ямки, расположенные в ряд на растоянии от 1,0 до 2,0 м друг от друга параллельно напольному рву, которые, если условно продлить их линию, совпадают с подобными ямками, ис следоваными в 1998 г. и атрибутироваными как каркасноплетневая стена, которая могла быть сооружена как в начале Х в., так и в конце ХІ в. и быть демонтированой до прокапывания первой группы канав. The newest excavations in northeastern corner of fortifications at korovel hillfort allowed studying both already known fortifications elements, and the new peculiarities: a system of ditches from wooden structures of horodnias (storerooms filled with soil) which can be divided into two groups.
First group includes ditches 5, 8, and 9 (under 0,2 m width), as far as ditches 8 and 9 are parallel and made side by side corresponding to the walls of two neighbouring horodnias. Ditch 5 is perpendicular to the ditch 8 and together with it con stitutes the walls of a single horodnia. Horodnias fillings are traced in the stratigraphy of the western wall of the excavation area 27. taking into consideration total levelling of the fortifications of the second half of the 10th c., these horodnias can be referred to the period when the ramparts were renewed at the end of the 11th c. Ditches 3, 4, 6, and 7 (0,3—1,0 m width) belong to the second group. Ditches 6 and 7 are almost perpendicular and have a common angle, hence belong to a single horodnia. Ditch 4 is parallel to the ditch 6 and belongs to the next bordering horodnia. Ditch 3 on the whole is perpendicular to the previous and almost parallel to the ditch 7, but dug in 2,0 m at the north part and 3,0 m at the south part far from the last one. such trapeziumshape can be an evidence of the constructive peculiarity of the horodnias at the place of the rampart’s curve.
Both groups of ditches are differently oriented to the four corners of the world and cross each other at an angle about 35—50 , testifying to the rebuilding of the rampart and its new route in the 12th c. because of destruction or to the overhaul of the northeastern angle of the fortifications. the latest period of the building the second group of ditches is confirmed by their correlation with the contours of the 12th and 13th c. horodnias’ fillings.
the filling of two rows of the 12th and 13th c. horodnias is recorded in the lower part of arable layer. the outward (north eastern) row reached the edge of the terrace; the size of the spot recorded is 3,00 × 2,00—2,25 m, which entirely corresponds the parameters of the most horodnias studied. Discovered at the level where the horodnias’ filling was recorded is an angle of mouldered wooden structure forming the angle of horodnia’s frame. the materials and ceramics of the period from the 10th to the 12th c. were found in the horodnias’ filling.
an attention is also paid to the pits from pillars situated in one line at the distance from 1,0 to 2,0 m from each other and parallel to the field side ditch. should their line be conditionally extended, they correspond with similar pits studied in 1998 and attributed as wireframe and wicker wall. this wall could be built either at the beginning of the 10th c., or at the end of the 11th c. and could be uninstalled before the first group of ditches were dug.